(untitled) (Al-Qamar, 2025)
Western scholars have been studying & writing about the life of Prophet Muhammad for many centuries. But there are few scholars in the west who have studied the life of Muhammad objectively. Martin Lings is included in the list of those famous western scholars. He has discussed different aspects of the life of Prophet Muhammad in his research work and writings. This research article aims to find out the life history, the contents of his book, and their historiographicl analysis. After briefly mentioning his thoughts, this paper proves that he uses authentic and reliable sources along with literary language, combines socio-cultural analysis with the reading of scriptures and Hadith, and includes stories of miracles.